Global Aging and Fiscal Policy with International Labor Mobility : A Political Economy Perspective - Tosun, Mehmet (IMF Working Papers; Working Paper ;, 2005)
This paper uses an overlapping generations model with international labor mobility and a politically responsive fiscal policy to examine aging in developed and developing regions. Migrant workers change the political structure composed of young and elderly voters in both labor-receiving and labor-sending countries. Numerical simulations show that the developed region benefits more from international labor mobility through the contribution of migrant workers as laborers, savers, and voters. The developing region experiences significant growth in all specifications but benefits more under international capital mobility. Restricting political participation of migrant workers in the developed region produces inferior growth results.